Managing functional decline among the elderly patients in ward 3 Geriatric ward using the Katz Index of Independence in Activities of Daily Living (ADL). Issue 1 (1st June 2011) - Cheah, E; Rajaram, S; Chua, H C; Ng, H L; Tim, H M; Fadillah, F; Zheng, D
Abstract : Introduction: The Katz Index of Independence in Activities of Daily Living commonly referred to as Katz ADL by Katz et al (1970) is the most appropriate instrument to assess functional status as a measurement of the person's ability to perform acts of daily living independently. Method: This Katz ADL was used in 15 geriatric patients aged between 78–84. The instrument employs a dichotomous (yes or no) scale, with 1 point given for each ADL in which the patient is independent. Six signifies independence in all ADLs: the lowest is 0 t full assistance is needed. The index ranks adequacy in performance in the six functions of bathing, dressing, toileting, transferring, continence and feeding. Six indicates full function, four indicate moderate impairment and two or less indicates severe impairment. 15 assessed, 9 had moderate impairment and 6 severe impairment, none of them had full function. Result: Nine had moderate impairment were given extensive rehabilitation. Physiotherapists and occupational therapists assessed them twice a day. Five continued to improve and were discharged with therapy appointments. Four worsened had to be downgraded to severe impairment. They also were not able to look after themselves and were discharged to long term care (nursing homes) 6 had severe impairment, 2 after a month of rehab were upgraded to moderate impairment and discharged with occupational therapy and physiotherapy appointments. Four were not able to manage on their own and had to be transferred to nursing homes. Conclusion: The Katz Index has emerged as an especially useful tool in assessing older adults, in determining nursing load and predicting length of hospitalisation, morbidity and mortality over time. The Katz Index has determined accuracy in predicting functional outcome over time among older adults.